(untitled) (Texas Journal of Medical Science, 2024)
This work examined the diagnostic role of biomarkers -APRI, alpha-fetoprotein–AFP and gammaglutamine transpeptidase–GGTP before and after antiviral therapy in patients with different degrees of liver fibrosis. At the same time, there was a decrease in these indicators after treatment, which indicates a reverse development of liver fibrosis after specific therapy.During therapy, a significant decrease in APRI from 0.67 to 0.33 (p<0.05), AFP from 4.82 to 1.77 (p<0.01) and GGTP from 42.4 to 26.8 was established (p<0.05). Thus, APRI, AFP and GGTP indicators can be used as dynamic markers for assessing the antifibroticeffect of etiotropic therapy for hepatitis C